Embracing INTO: library plans and campus collaboration to serve an increased international student population - Cranston, Catherine L., author; Farrell, Shannon L., author; Bullington, Jeffrey S., author; Regis University, publisher (Colorado State University. Libraries, 2013)
Universities are using private recruitment agencies to fast-track internationalization initiatives and realize tuition-based revenue increases. Colorado State University (CSU), with this dual aim of increasing the proportion of international students on campus and generating income via out-of-state tuition, signed a contract with INTO, a British organization that works to recruit international students to attend partner institutions from countries across five continents. International students, although not a homogenous population, as a whole do bring unique challenges. Our study examined how both campus and the library could prepare for the expected large influx of international students. Seeking to understand the INTO model and the effect it would have on campus, particularly in terms of resource planning, we conducted a series of interviews with INTO staff, librarians at other U.S. INTO institutions, and CSU faculty and staff who would interact most substantially with the INTO population. Various campus departments have made significant preparations to prepare for the growing INTO population, and we identified several steps that the CSU Libraries could take to better serve these students, including enhancing existing services and fostering new campus collaborations.
Keywords: INTO; international students; Colorado State University Libraries; collaboration